PROBLEMATIKA HUKUM AKTA HIBAH ATAS TANAH YANG TIDAK SAH KARENA MELEBIHI BAGIAN TERKECIL AHLI WARIS - Ratnasari Ratnasari; Akhmad Khisni (Jurnal Akta, 2017)
A grant is a legal act of transfer of ownership that is deliberately given to another party. In Article 1682 of Civil Code states that the implementation of the grant is done by using an authentic deed. The finding of this research on the verdict of Klaten District Court no. 8 / Pdt. G / 2001 / PN.Klt, where the land grant with Grant Deed no. 387 / DLG / 23/1999 and Grant Deed no. 388 / DLG / 23/1999 dated 30 August 1999 which has been made by defendant I (Land grantee) is declared null and void because it is illegal (legal defect) and has no legal power to be used as evidence of land grant rights. The conclusion in this research is the consideration of the judge in civil suit case with case No.8 / PDT.G / 2001 / PN. Klt constituted by the Civil Code (BW) which states the Grant Deed No 387 / DLG / 23/1999 and the Grant Deed No. 388 / DLG / 23/1999 shall be declared to have no legal force and shall be void by law because they have no material evidentiary power.Keywords : Legal Problems, Authentic deed, The heir’s minimum right